Preguntas naturales que les surgen a los estudiantes ante situaciones referentes a la aritmética - Ríos Bustos, John Beckenbauer (Universidad Antonio Nariño, 2023)
The research seeks to promote learning from the natural curiosity that the student brings to the classroom. Curiosity is an important aspect in cognitive development, however for several reasons, it is a subject that is not given the attention required as a process of acquisition of knowledge. For the learning of mathematics it is essential that students can nurture their curiosity and their ability to ask mathematical questions if there is a space where they can develop freely and their ideas are well received by their peers and educators.